Spatial distribution and predictors of early childbearing among Ethiopian women: evidence from the 2016 Ethiopian Demographic and Health Survey - Amare Teshome Tefera; Fanuel Gashaw; Martha Solomon; Nebiyu Bekele; Shegaye Shumet; Tigist Mulugeta; Araya Mesfin Nigatu; Solomon Gedlu Nigatu (BMC Pregnancy and Childbirth)
Abstract Background Age at first birth is a crucial factor in understanding fertility patterns within a population. Ethiopia reports high rates of maternal and child mortality alongside elevated fertility levels. Early childbearing is associated with increased health risks for both mothers and infants. However, there is limited information on the spatial distribution and predictors of early childbearing among Ethiopian women. Therefore, this study sought to assess the spatial distribution and determinants of early childbearing for women in Ethiopia using data from the 2016 Ethiopian Demographic Health Survey. Methods The study utilized data from the 2016 Ethiopia Demographic and Health Survey, incorporating 10,587 women in the analysis. Initially, spatial autocorrelation was employed to examine the geographic variation in early childbearing. To identify factors contributing to this spatial variation, both ordinary least squares and geographically weighted regression techniques were applied. The analysis for both regression methods was conducted using ArcGIS software. Results The mean age and age at first birth among the study participants were 27.93 (9.15 SD), and 18.98(3.81 SD) years respectively. About 40% (95%CI: 35, 44%) of the study participants had their first birth before the age of 18 years, with 86.15% of early childbearing found in rural residents. The study identified statistically significant hot spots of early childbearing in specific regions of Ethiopia, including parts of Amhara, Afar, southern Tigray, East Shewa, and southwest of Benishangul. The geographic weighted regression analysis found that religion (being Muslim), age at first cohabitation (before the age of 15 years, and between 15 and 17 years of age), and marital status (divorced) were the potential predictors that had a significant impact on geographic variation of early childbearing in Ethiopia. The geographically weighted regression model explained 65% of the geographic variation of early childbearing in Ethiopia. Conclusion Early childbearing was high in Ethiopia, and variation existed across its regions. The main hotspot for early childbearing was in the Amhara and Benishangul regions. Religion, age at first cohabitation, and marital status were the important predictors of early childbearing. Therefore, regional-specific strategies that target these variables should be considered while designing strategies aimed at reducing the level of early childbearing in Ethiopia.